A review on recent growth of electrical power generation and power demand in Bangladesh and some suggestions for combating the upcoming challenges. (February 2019) - Islam, Saiful
Abstract: A review of the recent growth of electrical power generation in Bangladesh has been presented which indicates a significant growth rate during the past three years. Because of this, the country has now nearly overcome the severe crisis in daily life, business and industrial production due to electrical power cut and load shedding. It has been indicated here that, side by side with the enhancement of generation capacity, the initiative and drive for expansion of transmission and distribution lines and supporting system have been taken by the Government which needs to be significantly strengthened. Maintaining a balance between the increase in load demand and increase in generation capacity has always been a challenge and it still exists. One of the biggest challenges at the moment is to prepare and train different categories of technical hands and engineers with the specialization of operating and maintaining the power stations, the transmission and distribution lines, the grid substations, the distribution substations. Preparing technical hands for the design of transmission and distribution lines, the grid substations, the distribution substations is also needed. These have been indicated in this paper.